Governmental investment into the environmental economy in the Western Balkan - Piksiades, Dušan; Šogorov Vučković, Jelena; Trifunović, Ivan (The European Journal of Applied Economics, 2022)
“A Green economy” has been one of the key agendas that governments all over the world have set the task to achieve. The last few decades have been critical to recognize this major problem, and they represented a critical part in reversing the effects brought on to our planet, with the acts of people and other natural factors. Governments have devised multiple plans to enforce regulations that would protect the environment we live in, and most of these plans were spearheaded by the United Nations (UN) and the European Union (EU). They devised several plans that have a task to minimalize, or escalate, effects of global warming until 2050. Covered by these plans are almost all of the World’s countries, and majority of these actions are connected with economy and sustainable development. The Western Balkan region has recently started implementing Eco laws and trying to make the environment more energy efficient. The WB countries have also undertaken serious economic improvement in the environmental field. This paper will analyze the progress of the Western Balkan countries and the way they have started, are implementing, and what is being planned to be done for future economical investment. The countries that will be analyzed are Albania, Bosnia & Herzegovina, Montenegro, North Macedonia, and Serbia. The analyses in the work would consider showing legal regulations and economical perspectives of the plans that need to be implemented in these countries, as well as their investment potential when it comes to the green economy. Since all of these countries tend to become members of the EU in the future, these results would be compared with the average measures performed by the EU countries. The paper hypothesizes that Western Balkan countries have lower average rates than EU countries, and would have to focus on making a more stable legal perspective when it comes to Eco laws, as well as a more environmentally stable economy.